Degradasi Zat Warna Metanil Yellow Secara Fotolisis Dan Penyinaran Matahari Dengan Penambahan Katalis TiO2-anatase dan SnO2 - Bhayu Gita Bhernama; Safni Safni; Syukri Syukri (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2015)
Degradation of Metanil yellow has been done. In this research the degradation process was done by photolysis and sunlighting method by using TiO2-SnO2 catalysis. The residu of metanil yellow was centrifuged and measured by UV/Vis Spectrophotometer at 300 – 600 nm after degradation. 6 mg/L of Metanil yellow and addition of 0,03 g TiO2-anatase and SnO2 for 150 min, gave the percentage of degradation 27,38 % and 25,00 % after photolysis. 6 mg/L of Metanil yellow and addition of 0,03 g TiO2-anatase and SnO2 for 150 min, gave the percentage of degradation 94,84% and 93,25% after lighted by sun with 1,13256 1015 foton cm-2/s intensity. From the results percentage of degradation showed that degradation with the addition of TiO2-anatase and SnO2 can improve the degradation of methanil yellow. The percentage of degradation proves that the addition of TiO2-anatase and SnO2 which is lighted by sun is better than photolysis process.